Penciptaan Video Klip Melayu Menggunakan Teknik Camera Follow Untuk Visualisasi Museum Raja Ali Haji - Grace Dea; Kanistren, Aragani Timur (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2025)
Music videos are an audiovisual art that enhances multisensory experiences while acting as a medium of cultural information and communication, such as Malay culture. In this creation, cinematographic techniques are employed, particularly the camera follow technique, to create an exploratory and immersive experience. This approach is implemented in the Malay music video “Nurlela” composed by Asbon Madjid and Bing Slamet, arranged in progressive Malay pop. The study aims to determine the effectiveness of creating a Malay music video using the camera follow technique to visualize the Raja Ali Haji Museum in presenting its historical collections and visitor regulations. The production process applies the Multimedia Development Life Cycle (MDLC), consisting of six stages: concept, design, material collecting, assembly, testing, and distribution. The testing stage uses the EPIC Model, which includes four dimensions: empathy, persuasion, impact, and communication.